Analisis Keterampilan Berpikir Kritis Siswa pada Pembelajaran IPAS SD Berbasis STEAM: Systematic Literature Review - Galang Budi Prakoso; Putri Manafe, Merliana; Idam Ragil Widianto Atmojo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is a crucial 21st-century competency urgently needing development in elementary schools, given low national science literacy scores. This study examines the application of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach in improving students' critical thinking in Natural and Social Sciences (IPAS) learning through a Systematic Literature Review (SLR) adapted from PRISMA 2020 guidelines. Twenty articles published between 2021 and 2026 were selected from Google Scholar, Garuda, and DOAJ based on inclusion and exclusion criteria. Results indicate the STEAM approach consistently and significantly improves critical thinking, showing moderate to high effectiveness. Project-Based Learning (PjBL) was identified as the most effective model combined with STEAM. Furthermore, Engineering and Science elements dominantly drive analysis, evaluation, and inference indicators. The Art element functions as an affective catalyst strengthening motivation and problem-formulation skills. This study confirms STEAM is highly suitable for integration into IPAS due to its interdisciplinary nature, aligning with the Merdeka Curriculum. Nevertheless, challenges like limited teacher competence, facilities, and the need for structured critical thinking scaffolding must be addressed for optimal implementation